Diseño urbano-arquitectónico de la franja periférica zona 3: administrativa - ciudad Francisco de Orellana (Coca) - Estrella Cadena, José Fernando (2016)
Francisco de Orellana Canton, located in northeastern Ecuador has experienced rapid growth in the last years, mainly for the oil exploitation in this region. However, this region has a deficit of public spaces and urban open spaces, and even more alarming is the lack of a plan of care for the environment, since this is an important topic due to the natural wealth of the region and to the rapid growth environmental impact. For this reason, it is indispensable to develop an adequate infrastructure planning in order to achieve sustainable development. In addition, the diagnosis of this city shows the flawed relationship between the city and the Payamino and Coca rivers. These rivers should be considered as a great potential to structure the fluvial green belt surrounding the city in order to establish a web of spaces that give structure not only to the city, but also to its borders and rivers. This shall provide a better standard of living for the inhabitants of the region, as well as the future generations. This is why this project seeks to generate a multi-centered city, composed of three centers; one at the North, characterized by knowledge and innovations; a second center located in the middle of the major city, focused on education and culture; and the last one located at the South, focused on management and services. Therefore, the name given to this thesis project is “Urban-Architectural Design of the Waterfront. ZONE 3, “Administrative”, which is conceived as city scale, its main approach is environmental management; since this is considered as indispensable in order to reach a sustainable development to solve, prevent, and minimize the environmental pollution, degradation, and exploitation. In this way a proper balance between economic development, population growth, rational utilization of resources, and the conservation and protection of the environment shall be established.